Novel miRNA Biomarkers for Patients With Duchenne Muscular Dystrophy - Meng, Qi; Zhang, Jiapeng; Zhong, Jingzi; Zeng, Dan; Lan, Dan (Frontiers in Neurology, 2022)
Creatine kinase (CK) has long been expected to be replaced by other fluid biomarkers for Duchenne muscular dystrophy (DMD) because it is independent of disease severity. Growing evidence has demonstrated that muscle-specific microRNAs, known as myomiRs, can perform as biomarkers for monitoring muscle pathology and disease severity of DMD patients. To gain insight into the relationships between serum myomiRs and clinical assessment, we measured serum levels of miR-1, miR-133a, miR-133b, miR-206, miR-208a, miR-208b and miR-499 in 48 DMD patients by using real-time quantitative reverse transcription polymerase chain reaction. These were then compared with age, muscle strength, muscle functions, CK levels, cardiac manifestations, and mutation types (deletions, duplications, and small mutations). When compared to 53 controls, the expression levels of myomiRs were all significantly elevated (p<0.05). The receiver operating characteristic curves of all seven myomiRs reflected marked differences between DMD patients and healthy controls (p<0.05). We also showed that serum levels of myomiRs were positively correlated with lower limb distal muscle strength in patients of all age groups. The levels of miR-499, miR-208b, miR-133a, and miR-133b had significant negative correlations with the time from supine position to upright (Gowers’ time) and the time taken to climb 4 stairs in older than 7 years-old DMD patients. Serum levels of miR-1, miR-133a, miR-133b, and miR-499 in cardiac involvement patients were remarkably higher than in noninvolved patient. There was no significant difference in levels of myomiRs between different mutation groups. Our results indicated that serum myomiRs could be considered as novel biomarkers for monitoring pathology/pathophysiology of DMD patients. In particular, miR-499, miR-208b, miR-133a, and miR-133b might have the ability to reflect the extent of muscle impairment.